Design and Analysis of Electromagnetic-Piezoelectric Hybrid Driven Three-Degree-of-Freedom Motor - Zheng Li; Peng Guo; Zhe Wang; Liang Zhao; Qunjing Wang (Sensors, 2020)
Multi-DOF movement actuators are widely used in industry, mainly in the fields of bionics and precision machining. With the non-stop improvement of modern-day industry, the requirements for the precision, integration and flexibility of multi-degree-of-freedom motion actuators in the industrial field have progressively increased. This paper presents a novel electromagnetic−piezoelectric hybrid driven three-degree-of-freedom motor. The driving method of the hybrid drive motor can be divided into electromagnetic driving and piezoelectric driving. The motor structure and working principle are analyzed. The structural parameters are obtained by modal analysis of the stators and rotor. The rationality of the stator structure is proved by using the transient analysis of the piezoelectric stators. The magnetic field characteristics of the motor are analyzed by both analytical method and the finite element method. The contact pressure and displacement between the piezoelectric stator and the rotor are analyzed by the analytical method. A motor drive model is established, which provides the basis for motor optimization design and control. Finally, a motor prototype and its test platform were built, and the experimental results are presented to verify the rationality of the motor design.